2000
DOI: 10.1007/pl00007416
|View full text |Cite
|
Sign up to set email alerts
|

Glial cell line-derived neurotrophic factor (GDNF) and its receptor (GFR-α1) are strongly expressed in human gliomas

Abstract: Glial cell line-derived neurotrophic factor (GDNF), a sequence-related factor of the transforming growth factor-beta family, has been identified as a potent neurotrophic factor for a variety of neuronal cell populations. At present, it is still unknown whether human gliomas in vivo are also capable of producing GDNF. We studied the expression of GDNF in 14 human glioblastomas, 1 gliosarcoma and 5 astrocytomas. Using an enzyme-linked immunosorbent assay, the amount of GDNF was quantified in human gliomas and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 42 publications
3
49
1
Order By: Relevance
“…Thus, the targeted expression of gas1 using the gfa2 promoter to drive its expression is an interesting approach to treat gliomas, because Gas1 blocks the proliferative action of GDNF, which is implicated in glioma cell migration and proliferation. 39,64 Also, it is reported that Gas1 antagonizes the Shh pathway, 34,65 which is involved in brain tumor formation and tumor growth. 66,67 Moreover, Gas1 inhibits cell proliferation and induces cell death (apoptosis and/or autophagy) even in the absence of active p53.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the targeted expression of gas1 using the gfa2 promoter to drive its expression is an interesting approach to treat gliomas, because Gas1 blocks the proliferative action of GDNF, which is implicated in glioma cell migration and proliferation. 39,64 Also, it is reported that Gas1 antagonizes the Shh pathway, 34,65 which is involved in brain tumor formation and tumor growth. 66,67 Moreover, Gas1 inhibits cell proliferation and induces cell death (apoptosis and/or autophagy) even in the absence of active p53.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that GDNF also affects the survival of cancer cells and their proliferation in gliomas (Wiesenhofer et al 2000b) and enhances the metastasis ) and invasion potential (Kikuchi 2004, Ito et al 2005, Qiao et al 2009, Lu et al 2010) of pancreatic cancer. GDNF and its receptor are expressed in human cancers such as gliomas (Wiesenhofer et al 2000a). It has also been reported that GDNF is overexpressed at the transcript level in non-small-cell lung carcinomas (Garnis et al 2005).…”
Section: Introductionmentioning
confidence: 98%
“…23 Furthermore, both genes are strongly expressed in human glioma. 24 Within each type of MEN 2, there are variations between members of the same family regarding the presence of 1 or several of the features of the disease and the age at onset. 25,26 Variations in phenotypes within the same family suggest a role for genetic modifiers, which may also work through quantitative effect.…”
mentioning
confidence: 99%